PENGARUH SUSTAINABILTY REPORT, INTELLECTUAL CAPITAL DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN ENERGI YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2019-2023 - Vanisa Riyadhita; Rohma Septiawati; Ihsan Nasihin (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2025)
This study aims to examine the sustainability report, intellectual capital and company size on the company's value whether or not it affects companies operating in the energy sector listed on the Indonesia Stock Exchange (IDX) during the 2019-2023 period. The method used in the research is the quantitative method. The population in this study is energy companies listed on the Indonesia Stock Exchange (IDX) during the 2019-2023 period. The sample used was 9 companies, the selection of samples was taken based on selection techniques through a number of predetermined criteria (purposive samoling). The data used is secondary data with data collection techniques in the form of documentation. The software used to analyze the relationship between independent variables and dependent variables is SmartPLS version 4 using outer model analysis, inner model analysis and hypothesis testing. The results of the study show that sustainability report and intellectual capital have a negative effect on company value, while company size has a positive effect on company value.